SEJARAH SOSIAL PERADABAN ISLAM DINASTI IBN THULUN DARI BERDIRI SAMPAI RUNTUH - Maini Wati; Afrizal, Syawaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Ibn Tulun Dynasty was the first autonomous dynasty to rule Egypt and its surrounding regions, such as Syria and Hijaz, in the 9th century CE, existing from 868 until its fall in 905 CE. This dynasty was founded by Ahmad ibn Tulun, who was initially appointed as governor by the Abbasid Caliphate but later declared his political independence. The reign of the Ibn Thulun Dynasty was marked by significant advancements in military, political, economic, and architectural fields, including the construction of the city of al-Qata’i and the magnificent Ibn Thulun Mosque. Ahmad ibn Thulun implemented effectiv public policies to maintain political stability and security, strengthen the military, and develop agricultural and trade infrastructure. However, this dynasty only lasted about 38 years due to the lack of a strong national foundation and the inability of its successors to maintain power, ultimately being reclaimed by the Abbasids. This research uses a qualitative descriptive method with literature study to examine the establishment process, development, contributions, and causes of the collapse of the Ibn Tulun Dynasty in the context of Islamic civilization history in Egypt.